The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/molbev/msab002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Divergence of Multiple Duplicated Foxl2 Homeologs and Alleles in a Recurrent Polyploid Fish

Abstract: Evolutionary fates of duplicated genes have been widely investigated in many polyploid plants and animals, but research is scarce in recurrent polyploids. In this study, we focused on foxl2, a central player in ovary, and elaborated the functional divergence in gibel carp (Carassius gibelio), a recurrent auto-allo-hexaploid fish. First, we identified three divergent foxl2 homeologs (Cgfoxl2a-B, Cgfoxl2b-A, and Cgfoxl2b-B), each of them possessing three highly conserved alleles and revealed their biased retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 94 publications
2
40
0
Order By: Relevance
“…In this study, we identified two homeologs of Cgviperins with about 91% identity, and each homeolog has three alleles with high identities (≥99.0%) and located on three homologous chromosomes separately (Supplementary Figure S1 and Figure 1C). Compared to zebrafish, our results (Figures 1B, D) indicated that the duplication of Cgviperin, same as gibel carp other genes (i.e., dmrt1, foxl2, nanos2 and bmp15) (55,60,69,70), may derive from the early allotetraploidy (4R) and a late autotriploidy (5R) event. In addition, Cgviperin-A and Cgviperin-B showed a different tissue-dependent constitutive expressions, suggesting A or B homologs might occur dominant or biased expression of homeologs during gibel carp evolution.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In this study, we identified two homeologs of Cgviperins with about 91% identity, and each homeolog has three alleles with high identities (≥99.0%) and located on three homologous chromosomes separately (Supplementary Figure S1 and Figure 1C). Compared to zebrafish, our results (Figures 1B, D) indicated that the duplication of Cgviperin, same as gibel carp other genes (i.e., dmrt1, foxl2, nanos2 and bmp15) (55,60,69,70), may derive from the early allotetraploidy (4R) and a late autotriploidy (5R) event. In addition, Cgviperin-A and Cgviperin-B showed a different tissue-dependent constitutive expressions, suggesting A or B homologs might occur dominant or biased expression of homeologs during gibel carp evolution.…”
Section: Discussionmentioning
confidence: 76%
“…One of the two duplicates may be fractionated (deleted), or both may be retained, or diverge and evolve (sub- or neofunctionalization) ( 3 ). Recently, we revealed the biased expression and sub-/neofunctionalization of multiple duplicated foxl2 homeologs and alleles in gibel carp ( 60 ). Innate immunity plays a vital role in the first barrier protecting the host from invading viruses ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hexaploid gibel carp (C. gibelio) was originated from sympatric progenitor tetraploid crucian carp (Carassius auratus) via autotriploidy about 0.5 million years ago (Mya) (Li et al, 2014). Genomic anatomy and single-gene analysis revealed that gibel carp was an allohexaploid (AAABBB) in comparison with the allotetraploid crucian carp (AABB) (Li et al, 2014;Gan et al, 2021;Yu et al, 2021;Wang et al, under review). Three alleles in subgenome A and three alleles in subgenome B make the genome unable to pair during meiosis (Gan et al, 2021) and the hexaploid gibel carp conquers the reproductive obstacles via unisexual gynogenesis (Gui and Zhou, 2010;Zhou and Gui, 2017), in which unreduced eggs are activated by the sperm of sympatric sexual species to initiate embryogenesis with only maternal genetic information.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic anatomy and single-gene analysis revealed that gibel carp was an allohexaploid (AAABBB) in comparison with the allotetraploid crucian carp (AABB) (Li et al, 2014;Gan et al, 2021;Yu et al, 2021;Wang et al, under review). Three alleles in subgenome A and three alleles in subgenome B make the genome unable to pair during meiosis (Gan et al, 2021) and the hexaploid gibel carp conquers the reproductive obstacles via unisexual gynogenesis (Gui and Zhou, 2010;Zhou and Gui, 2017), in which unreduced eggs are activated by the sperm of sympatric sexual species to initiate embryogenesis with only maternal genetic information. Compared with sexual tetraploid crucian carp, gynogenetic hexaploid gibel carp exhibits wider geographic distribution and higher genetic diversity (Jiang et al, 2013;Liu et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%